Evaluates the chemical fractions of arsenic bounded to solid matrixes of thar coalfield of pakistan by sequential extraction method. Issue 6 (20th April 2017) - Ali, Jamshed; Kazi, Tasneem G.; Afridi, Hassan I.; Baig, Jameel A.; Shah, Faheem; Arain, Mariam S.
Abstract : The main objective of this work was to evaluate the bounded fractions of arsenic (As), physicochemical parameters, and mineral composition of solid matrices of coal mining area of Pakistan. Clay, sand, and soil samples were collected from different depths of blocks 3 and 5 of Thar coalfield. The As bounded with different chemical fractions of solid matrices was extracted by sequential extraction scheme, proposed by the Community Bureau of Reference protocol (BCR). Certified reference material and spiking tests were performed to check the accuracy of methodology. Extracted As fractions from all studied solid material by sequential extraction method were measured by hydride generation atomic absorption spectrometry. Mineral composition has been determined by scanning electron microscopy and X‐ray diffraction. All the three solid samples obtained from both blocks varied in their physicochemical parameters and As contents in different chemical forms. The total As and extractable As concentration in block 3 was higher as compared to block 5. The recovery and standard deviation between total As and ∑(1–4) fractions in all studied samples were obtained as >95% and <5%, respectively. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 1667–1675, 2017